Pengaruh Budaya Organisasi dan Motivasi dengan Kedisiplinan sebagai Variabel Intervening terhadap Kinerja Pegawai pada Dinas Pemerintahan Kota Palembang - Melati, Melati; Rahayu, Sri; Choiriyah, Choiriyah (Training & Research Institute - Jeramba Ilmu Sukses, 2022)
The purpose of this study was to determine the effect of organizational culture, motivation with discipline as an intervening variable on the performance of employees at the Palembang city government service either partially or simultaneously. This research method uses quantitative method with expo Pacto approach . Data collection techniques using questionnaires and documentation. The data analysis technique used the SPSS For Windows Version 21 program. Based on the results of the study, it was found that organizational culture, motivation with discipline as an intervening variable had a positive and significant effect on employee performance at the Palembang city government service.